Antecedents of Trust: A Case study between Karachi and Dubai Facebook Shoppers - Nawaz Ahmad; Saniya Mehboob; Farhan Zeb Khaskhelly (Institute of Business Management, 2019)
In the adoption of online shopping, the main issue faced by consumers is the development of trust. Consumers are unable to physically examine the products before making a purchase. The study aims to find out the factors that develop trust in Facebook shopping through case study analysis.  A designed questionnaire was circulated to gather the data from participants. The participants included in the study were the shoppers of Facebook. An aggregate of 270 structured questionnaires was circulated in Karachi and Dubai out of which 225 were considered in the study. For the data analyses, demographic statistics frequency and bar chart and descriptive statistics, have been applied. The study concludes that online firms need to design separate strategies plus framework and for both the cities. Countries despite having similar cultural values vary greatly due to geographical distances. Online suppliers must focus on developing interpersonal trust by providing exchange and return policies to consumers that will reduce the risk to an extent and build trust between the store and Facebook shoppers.